Recovering the Calvin of "Two Kingdoms"? : a historical-theological inquiry in the light of church-state discourse in South Africa - Jooste, Simon (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.